THE EFFECT OF COMPENSATION, MOTIVATION AND WORK SATISFACTION TO THE PERFORMANCE AT INVESTMENT AND INTEGRATED ONE-STOP SERVICE OFFICE REGENCY OF DHARMASRAYA - ., Mitra Murni; Heryanto, (Archives of Business Research, 2019)
This research is aimed to know the significance of effect: Compensation to performance, Work Motivation to performance, Work Satisfaction to employees’ performance, Compensation, Motivation and Work Satisfaction to the employees’ performance. This is a survey research within questionnaires as the technique to 39 respondents who were the employees of Investment And Integrated One-Stop Service Office Regency of Dharmasraya. This is quantitative descriptive research. In order to obtain a valid and reliable instrument, validity and profitability tests. The technique of data analysis was simple linear regression and multiple linear regression with t-test, f-test and Adjusted R2. The result of the research shows that there are positive effects from compensation, motivation and work satisfaction simultaneously to the employees’ performance at Investment And Integrated One-Stop Service Office Regency of Dharmasraya.